The Expulsion and Forced Conversion of the Jews of Isfahan: A Comparison between Arakʿel Dawrižecʿi's Girk' patmuteanc' and Bābāʾī ben Loṭf's Ketāb-e anūsī - Lucca, Paolo (Entangled Religions, 2022)
The article deals with the persecution and expulsion of the Jews of Isfahan that took place under Shah ‘Abbās II in the years 1656-1662. The events, which occurred at Grand Vizier Moḥammad Beg’s instigation, are told of in a number of contemporary sources, the most important of them being Bābā’ī ben Loṭf’s Ketāb-e anūsī (in Judeo-Persian) and Arak‘el Davrižec‘i’s Girk‘ patmuteanc‘ (in Armenian). The article tries to find a rationale for the differences found between these two accounts, focusing on how the two authors report the murder of a Jewish informer to the Grand Vizier that was perpetrated by other Jews. By analysing how they fashion a different narrative drawing on the same events, the article proposes that their opposite attitudes towards the murderers come from their different intent and approach in writing their works. Bābā’ī’s account follows in the wake of the traditional biblical paradigm of sin and punishment, thus showing less sympathy for the plight of the Jews than one could expect, as from the author’s perspective their suffering was supposedly brought on them by their own sins. On the other hand, Aṙak‘el’s more empathic representation of the Jews and their tribulations could be understood in the light of his own concern about his coreligionists being tempted to convert to Islam for material benefit or economic convenience. This is the reason why Aṙak‘el stresses how the Jews held to their faith and were not lured by the money and gifts the Persians offered them to turn to Islam. He fashions the chapter he devoted to the history of the Jews of Isfahan as a moral tale, complete with a hero and a villain and enhanced with some Jewish flavour details, to show his fellow Armenians how they, too, should resist the allurement of conversion.